2016
DOI: 10.1038/srep37456
|View full text |Cite
|
Sign up to set email alerts
|

NapB in excess inhibits growth of Shewanella oneidensis by dissipating electrons of the quinol pool

Abstract: Shewanella, a group of ubiquitous bacteria renowned for respiratory versatility, thrive in environments where various electron acceptors (EAs) of different chemical and physiological characteristics coexist. Despite being extensively studied, we still know surprisingly little about strategies by which multiple EAs and their interaction define ecophysiology of these bacteria. Previously, we showed that nitrite inhibits growth of the genus representative Shewanella oneidensis on fumarate and presumably some othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…By this logic, we focus on the respiratory chain, especially terminal oxidases. This coincides with the findings of systematic investigations into nitrite and NO physiology in Shewanella oneidensis, a facultative Gram-negative γ-proteobacterium renowned for respiratory versatility [15][16][17][18][19][20] . In this bacterium, the primary target of nitrite is heme-copper oxidase (HCO) cbb 3 (hereafter referred to as cbb 3 ), whereas NO indistinguishably interacts with all cytochromes c 15,16,19,20 .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…By this logic, we focus on the respiratory chain, especially terminal oxidases. This coincides with the findings of systematic investigations into nitrite and NO physiology in Shewanella oneidensis, a facultative Gram-negative γ-proteobacterium renowned for respiratory versatility [15][16][17][18][19][20] . In this bacterium, the primary target of nitrite is heme-copper oxidase (HCO) cbb 3 (hereafter referred to as cbb 3 ), whereas NO indistinguishably interacts with all cytochromes c 15,16,19,20 .…”
supporting
confidence: 86%
“…These data, all together, manifest that nitrite modulates aminoglycoside susceptibility by compromising cbb 3based respiration, implying that cbb 3 , the bc 1 complex, or both could be targets of nitrite. This study focused on cbb 3 , because it has been shown to be susceptible to nitrite [15][16][17][18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
“…Distinct susceptibilities of S. oneidensis and E. coli to nitrite and NO. Previously, we demonstrated that S. oneidensis is highly susceptible to nitrite (NaNO 2 and KNO 2 ) during aerobiosis (29)(30)(31)(32). For comparison, we assessed the susceptibility of E. coli to nitrite under the same conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, nitrite has been found to be extremely toxic to S. oneidensis cells grown under either aerobic or anaerobic conditions. While the primary target of nitrite for oxygen respiration is heme-copper oxidase (HCO) cyt cbb 3 , nitrite inhibition of alternative EA respiration involves cAMP-Crp (catabolite repression protein) regulation and NapB, a soluble c-type cyt that, in excess, dissipates electrons of the quinol pool (29)(30)(31).…”
mentioning
confidence: 99%
“…In S. oneidensis, the primary target of nitrite has been identified as cytochrome cbb 3 , an HCO that is highly efficient for oxygen respiration (22)(23)(24). For respiration of nonoxygen electron acceptors (EAs), nitrite inhibition involves cyclic AMP-catabolite repression protein (cAMP-Crp) regulation and NapB, a soluble cytochrome c that in excess dissipates electrons of the quinol pool (25,26).…”
mentioning
confidence: 99%